Students' digital media literacy abilities in Islamic religious education lessons reviewed from learning style - Annisa’ Fitriyah Anwari; Moh. Sahlan; Indah Wahyuni (Research and Development in Education (RaDEn), 2025)
This research is considered necessary because it is in line with the current digital era where many of the students certainly take advantage of the digital media around them. With a sufficient understanding of digital media literacy, it is hoped that it will help them in choosing and evaluating information wisely, thereby reducing the risk of exposure to inaccurate or dangerous information because it is seen from the rapidly increasing digital development. This study aims to find out the extent of students' digital media literacy and also the various learning styles of students and the analysis of students' digital media literacy according to their respective learning styles (visual, auditory and kinesthetic). The method used descriptive qualitative research with 48 respondents. The data collection technique uses questionnaires (multiple choice digital media literacy questionnaire and learning style questionnaire to determine the types of students' learning styles including visual, auditory, kinesthetic, and mixed) and analysis using the help of SPSS version 25.  The results of this study show that the learning style that has a higher understanding of digital media literacy than other learning styles is the auditory learning style with an average of 19.80, the second is the visual learning style with an average of 19.75, the third is the mixed learning style with an average of 19.57, and the last is the kinesthetic learning style with an average of 19.17.